Foreign and domestic ownership as the mediator Between investment strategy and company performance - Ismail Badollahi; Idil Rakhmat Susanto; Nurhidayah Nurhidayah; Wahyuni Wahyuni (Manajemen dan Bisnis, 2022)
The study aims to examine the moderating effect of the ownership structure on the relationship strategi investasi and the comprehensive firm performance in ASEAN. Using data from financial reports and sustainability report. Samples are 34 nonfinancial companies in ASEAN 2007 until 2019. The sample testing method is unbalanced panel data regression to test hypothesis. Th results shows Foreign and domestic ownership moderate the relationship between strategi investasi and productivity and kinerja keuangan. This research also proves that foreign and domestic ownership cannot form the relationship between strategi investasi and kinerja lingkungan. This study gives additional evidence as confirmation of the theory of Industrial Organization about the implementation of the corporate strategy is influenced by external factors, namely the role of foreign ownership in improving corporate performance. This study gives new insight to the company about the importance of considering the strategi investasi based R&D and the role of foreign and domestic ownership to increase productivity, kinerja keuangan and kinerja lingkungan.